The relationship between prompt treatment and preserving the lives of burn patients - Turki Mohammed Ahmed Alkhayri; Saeed Abdullah Mohammed Alamri; Abdulrhman Ali Abdulrhman Alshaikhi; Ahmed Bajan Alwan Alabdali; Ali Sani Ali Alkatheeri; Mohammed Abdulaziz İbrahim Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
First aid should be administered as soon as possible after the accident for best results in burn care. A sufficient understanding of how to treat burns using first aid helps lessen the severity of the injury. Thus, the purpose of this study is to determine the extent of first aid professionals’ knowledge, attitudes, and information sources regarding treating burn patients in Saudi Arabia. To evaluate the knowledge, attitudes, and information sources on first aid for burns among those sent to the Burns Center in Saudi Arabia, a questionnaire-based survey was carried out.. In this survey, the appropriate sampling method was adopted. The variables consist of one variable, namely the age of first aid providers. The study showed that there are no statistical indications of the age of the aid providers on the extent of knowledge of the correct or proper ways of providing services. The survey responded to a total of 400 individuals. The average age of participants was 30 years. The study showed that there was awareness of the initial procedures for dealing with burns, both with regard to recording all information about the injury and also the correct handling of burns, identifying the nature and degree of burning and dealing with the degree appropriately.The results of the study showed that the average responses of the sample of paramedics to the study are positive with regard to high rates of awareness of the correct controls and procedures for dealing with burns sufferers at the time of crisis, indicating an increase in the awareness of paramedics of the importance of following the right and proper steps in the initial diagnosis of burns.